2023
DOI: 10.3390/microorganisms11061414
|View full text |Cite
|
Sign up to set email alerts
|

High Disinfectant Tolerance in Pseudomonas spp. Biofilm Aids the Survival of Listeria monocytogenes

Gunn Merethe Bjørge Thomassen,
Thorben Reiche,
Martinus Hjørungnes
et al.

Abstract: Pseudomonas spp. are the most commonly found bacteria in food-processing environments due to properties such as a high growth rate at low temperatures, a high tolerance of antimicrobial agents, and biofilm formation. In this study, a set of Pseudomonas isolates originating from cleaned and disinfected surfaces in a salmon processing facility were screened for biofilm formation at 12 °C. A high variation in biofilm formation between the isolates was observed. Selected isolates, in both planktonic and biofilm st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 57 publications
(80 reference statements)
0
6
0
Order By: Relevance
“…Similar to our results, previous work has shown that biofilms composed of strains of L. monocytogenes and Pseudomonas aeruginosa were dominated by Pseudomonas , which represented 99 % of the biofilm composition [ 9 ]. Similarly, Thomassen et al (2023) [ 70 ] grew multi-species biofilms composed of one strain of L. monocytogenes and five strains of Pseudomonas spp. for three days and determined that L. monocytogenes concentration represented 0.9 % of the total biofilm biomass [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to our results, previous work has shown that biofilms composed of strains of L. monocytogenes and Pseudomonas aeruginosa were dominated by Pseudomonas , which represented 99 % of the biofilm composition [ 9 ]. Similarly, Thomassen et al (2023) [ 70 ] grew multi-species biofilms composed of one strain of L. monocytogenes and five strains of Pseudomonas spp. for three days and determined that L. monocytogenes concentration represented 0.9 % of the total biofilm biomass [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Thomassen et al (2023) [ 70 ] grew multi-species biofilms composed of one strain of L. monocytogenes and five strains of Pseudomonas spp. for three days and determined that L. monocytogenes concentration represented 0.9 % of the total biofilm biomass [ 70 ]. Nonetheless, it should be noted that in these two studies [ 9 , 70 ], culture-based techniques were used to quantify bacteria and likely did not account for potential persister cells within the biofilms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interactions between L. monocytogenes and Pseudomonas spp. within biofilms have been studied in laboratory models [11,12,79,80], highlighting the protective effect of Pseudomonas spp., particularly P. fluorescens, towards L. monocytogenes. The effect of other members of the resident microbiota of FPE can either enhance or inhibit the survival of L. monocytogenes [81,82].…”
Section: Discussionmentioning
confidence: 99%
“…The resident microbiota that coexists with L. monocytogenes in environmental settings may have a role in the survival of this pathogen. For example, a protective effect of Pseudomonas biofilms on L. monocytogenes has been observed, which suggested that control of Pseudomonas in the FPE could reduce contamination of L. monocytogenes [11,12]. Studies using amplicon sequencing or metagenomics alongside culture enrichments have explored the resident microbiota coexisting with L. monocytogenes in various FPE [2], including fish and meat processing settings, dairy factories [13] and fruit packing facilities [14].…”
Section: Introductionmentioning
confidence: 99%